Protective role of surface Toll-like receptor 9 expressing neutrophils in local inflammation during systemic inflammatory response syndrome in mice. (October 2017) - Meng, Xiuping; Sun, Wei; Ren, Yunjia; Xiao, Yue; Zhao, Peiyan; Lu, Wenting; Hua, Li; Wang, Luowei; Wang, Liying; Yu, Yongli
Highlights: D-GalN-presensitized mice induced with CpG ODN developed SIRS symptoms. Neutrophils were massively recruited into the peritoneal cavity of the SIRS model mice. Early recruited sTLR9 + peritoneal neutrophils were protective as a subpopulation. sTLR9 expression on peritoneal neutrophils was upregulated by a life-saving CCTODN. Transferring sTLR9 high neutrophils containing PLCs rescued the SIRS model mice. Abstract: Clinically, systemic inflammatory response syndrome (SIRS) occurs after serious trauma or sepsis. In sepsis, neutrophils are the major effector cells responsible for eliminating pathogens. However, the role of neutrophils in development of SIRS, especially in local inflammatory area, is controversial. In this study, we established a SIRS mouse model characterized with cytokine-mediated lethal shock by intraperitoneal injection of oligodexynucleotides containing CpG motifs (CpG ODN) in D-galactosamine (D-GalN) sensitized mice based on our previous work and found that abundant neutrophils were rapidly recruited into the peritoneal cavity, where some neutrophils expressed surface TLR9 (sTLR9), defined as sTLR9 + neutrophils. Along with the progression of SIRS, the expression of sTLR9 in sTLR9 + neutrophils isolated from peritoneal lavage cells (PLCs) was declined in accompany with an increase in the level of the inflammatory cytokine TNFα and a decrease in the level of the anti-inflammatory cytokine IL-10 in Ly6G + PLCs. When using CCT ODN, an oligodeoxynucleotide with CCT repeats, which we have previously shown to be capable of rescuing mice from lethal shock, the expression of sTLR9 on neutrophils was significantly elevated. Adoptive therapy using early recruited neutrophil-rich PLCs containing sTLR9 + neutrophils that express high levels of sTLR9, could rescue mice from SIRS. Overall, the data reveal that the early recruited sTLR9 + neutrophils may, at least in the area of local inflammation, play a protective role during SIRS development and provide a method to rescue the patients with severe SIRS via the up-regulation of sTLR9 levels on the surface of neutrophils or via adoptive therapy with protective sub-populations of neutrophils.